2013
DOI: 10.1186/bcr3453
|View full text |Cite
|
Sign up to set email alerts
|

Obesity enhances nongenomic estrogen receptor crosstalk with the PI3K/Akt and MAPK pathways to promote in vitro measures of breast cancer progression

Abstract: Introduction: Epidemiological and clinical studies indicate that obesity is associated with a worse postmenopausal breast cancer prognosis and an increased risk of endocrine therapy resistance. However, the mechanisms mediating these effects remain poorly understood. Here we investigate the molecular pathways by which obesityassociated circulating factors in the blood enhance estrogen receptor alpha (ERα) positive breast cancer cell viability and growth. Methods: Blood serum was collected from postmenopausal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 55 publications
0
43
1
1
Order By: Relevance
“…In contrast, the lack of difference in serum estradiol levels by BMI does not agree with the literature, as researchers have generally found that obese postmenopausal women have higher estradiol levels (39)(40)(41). However, of the 25 women that provided the sera for this study, 9 obese patients and 1 normal-weight patient were receiving an aromatase inhibitor (21), which may have masked any difference in estradiol levels between the groups.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…In contrast, the lack of difference in serum estradiol levels by BMI does not agree with the literature, as researchers have generally found that obese postmenopausal women have higher estradiol levels (39)(40)(41). However, of the 25 women that provided the sera for this study, 9 obese patients and 1 normal-weight patient were receiving an aromatase inhibitor (21), which may have masked any difference in estradiol levels between the groups.…”
Section: Discussioncontrasting
confidence: 52%
“…Consequently, this difference in macrophage COX-2 expression and PGE2 production may be because of elevated levels of these free fatty acids in the obese patient sera. There is also some evidence that the inflammatory cytokines IL6 and TNFa, found in higher concentrations in our obese patient serum samples (21), can induce COX-2 expression (27,35,36). This suggests that more than one mechanism may be responsible for the obesity-associated upregulation of macrophage COX-2 expression and PGE2 production seen in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, our results align with the finding in patients that adipocytes located near tumor cells up-regulate IL-6 production (27, 42, 55). The link between IL-6 and obesity is well-established (6062). In addition, transcriptomic analysis revealed marked up-regulation of IL-6 inflammatory pathway in the tumors of BC patients with obesity in comparison to those without obesity (63).…”
Section: Discussionmentioning
confidence: 99%